Analisis Geomorfologi dan Klasifikasi Bentuklahan Daerah Olele, Kecamatan Kabila Bone, Kabupaten Bone Bolango - Jihad Ramadhan Abduh; Yayu Indriati Arifin; Ninasafitri Ninasafitri (Universitas Negeri Gorontalo, 2025)
The study area exhibits diverse geological conditions, one of which is reflected in its geomorphological characteristics that are important to investigate. Olele is located within the southern mountainous zone of Gorontalo and is characterized by hilly to steep terrain. This study aims to identify and classify landform units based on geomorphological analysis. The research method involved field-based geological surveys, including direct geomorphological observations, lithological identification, and geomorphological mapping supported by secondary data analysis. The results show that the study area consists of three geomorphological landform units, namely alluvial plains covering an area of 17.84 ha, reef terrace plains with an area of 17.43 ha, and fault zone hills occupying 1,072.23 ha. The morphography of the area ranges from lowlands to high hills with elevations between 0 and 960 meters above sea level. Slope gradients vary from flat to very steep. Morphogenetic analysis indicates that endogenous processes, particularly tectonic activity, play a significant role in shaping the landscape, as evidenced by the presence of joint structures. Lithologically, the area is composed of unconsolidated alluvial deposits, reef limestone, and volcanic rocks that have undergone weathering and erosion. These findings demonstrate that the geomorphology of the Olele area is strongly controlled by tectonic processes, lithological variation, and surface processes, which together contribute to the development of distinct landform units.